The Transient Receptor Potential Channel Yvc1 Deletion Recovers the Growth Defect of Calcineurin Mutant Under Endoplasmic Reticulum Stress in Candida albicans - Peng, Liping; Du, Jiawen; Zhang, Runfan; Zhu, Nali; Zhao, He; Zhao, Qiang; Yu, Qilin; Li, Mingchun (Frontiers in Microbiology, 2021)
Transient receptor potential (TRP) channel Yvc1 was related with hyphal growth, oxidative stress response and pathogenicity. Calcineurin subunit Cnb1 was activated immediately in yeasts when exposed to severe stimulation. However, the relationship between Yvc1 and Cnb1-governed calcium ions and endoplasmic reticulum (ER) stress response remains unrevealed. In this study, we found the mutant cnb1Δ/Δ was sensitive to tunicamycin, which was related with the over-expression of membrane calcium ions channel to increase cytosol calcium concentration. However, the growth of cnb1Δ/Δyvc1Δ/Δ mutant was recovered and cell vitality was better than cnb1Δ/Δ strain, meanwhile the cellular calcium concentration was decreased and its fluctuation was weakened under ER stress in the cnb1Δ/Δyvc1Δ/Δ strain. To verify the regulation role of Yvc1 in the calcium concentration, we found the addition of CaCl2 led to the worse viability, while the growth state was relieved under the treatment of EGTA in cnb1Δ/Δ strain. In conclusion, the deletion of YVC1 could reduce the cellular calcium and relieve the ER stress sensitivity of cnb1Δ/Δ strain. Thereby, our findings shed a novel light on the relationship between the Yvc1-governed cellular calcium concentration and ER stress response in C. albicans.